Statistics and strenght of materials for architecture and building constructions - Onouye, Barry; Kane, Kevin (Boston, Massachusetts : Prentice-Hall, 2012)
A primary aim of this book since its first publication in 1998 has been to develop and present basic structural concepts in an easily understood manner using building examples to supplement the text.
Introduction -- Statics -- Analysis of selected determinate structural systems -- Load tracing -- Strength of materials -- Cross-sectional properties of structural members -- Bending and shear in simple beams -- Bending and shear stresses in beams -- Column analysis and design -- Structural connections -- Structure, construction and architecture.
Includes index.
Keywords: ARCHITECTURE